3D Surface Reconstruction Using Infrared (IR) Signal - Mohd Shaber, Nasuha (Universiti Teknologi PETRONAS, 2017)
Three-Dimension (3D) surface reconstruction from object using an infrared sensor is becoming one of the widely used in research today. In this project data collected from infrared sensor will be used to reconstruct a 3D surface of an object. The sensor value data need to be converted into distance between infrared sensor to the surface of an object. One-Dimensional (1D) to two-dimensional (2D) conversion is carried out by using the angle between collection of each data and the distance between sensor and an object. The method to be used to reconstruct a 2D image by using conversion between Polar (angle-distance-axis) to Cartesian coordinate (x-yaxis) plane. The 2D images that were obtained will be used to reconstruct threedimensional (3D) surface using a mesh grid algorithm and by acquiring the z-axis of the object.